2011
DOI: 10.1093/cid/ciq036
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Infected Hospitalized Patients with 2009 Pandemic Influenza A (pH1N1)—United States, Spring and Summer 2009

Abstract: We describe the clinical findings of HIV-infected patients hospitalized with 2009 pandemic influenza A (pH1N1). Data were derived from 3 separate case series in the United States. Among 911 adults hospitalized with pH1N1 influenza, 31 (3.4%) were HIV infected compared with an HIV prevalence of 0.45% in the general US adult population. HIV-infected influenza patients experienced similar rates of intensive care unit admission (29% vs 34%) and death (13% vs 13%) compared with non-HIV-infected patients. Among HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
0
33
2
Order By: Relevance
“…The results of the study showed that receiving ART approximates significance in terms of being admitted to an ICU and/or death. The majority of the patients receiving ART therapy were HIV-infected patients with a CD4 cell count <200 cells/µL, while in the present study, the median value for CD4 counts was more than 600; this could explain the differences in the findings [20].…”
Section: Discussioncontrasting
confidence: 68%
“…The results of the study showed that receiving ART approximates significance in terms of being admitted to an ICU and/or death. The majority of the patients receiving ART therapy were HIV-infected patients with a CD4 cell count <200 cells/µL, while in the present study, the median value for CD4 counts was more than 600; this could explain the differences in the findings [20].…”
Section: Discussioncontrasting
confidence: 68%
“…92 We finally included 26 zanamivir trials: 14 on treatment in adults, [71][72][73]77,[80][81][82]87,89,91,95,[97][98][99] two in children 78,84 and 10 trials in prophylaxis. 70,79,85,86,88,90,93,94,96,100 Our attempt at collecting sufficient information from regulatory files to reconstruct missing CSRs also failed because the information appeared to be insufficient for a reliable reconstruction.…”
Section: Zanamivirmentioning
confidence: 99%
“…Several of the zanamivir trials were also under-recruited. We noted the use of different relief medication across different centres within the same trial, and in one zanamivir trial, 85 according to the protocol, participants receiving antibiotics for bacterial respiratory tract infection should have been excluded but in the trial this did not happen. In the zanamivir trial, 86 the definition of 'confirmed influenza' was amended after protocol closure.…”
Section: Other Potential Sources Of Biasmentioning
confidence: 99%
“…Several observational studies have shown no difference in clinical course of pH1N1 infection between HIV‐positive and HIV‐negative patients, either adults or children . On the other hand, a study of hospitalizations due to pH1N1 conducted in the US reported a disproportionately high admission rate among HIV‐positive patients, while an observational study conducted in Mexico city documented poorer outcome among HIV‐positive patients not on highly active antiretroviral treatment (HAART) and with PCR‐detectable HIV . The impact of pH1N1 infection therefore appears to be at least partially influenced by treatment and immunovirological status.…”
Section: Introductionmentioning
confidence: 99%